Destructive and non-destructive tests on columns and cube specimens made with the same concrete mix. (26th September 2022) - Frappa, Giada; Miceli, Massimiliano; Pauletta, Margherita
Highlights: Capacity of destructive and non-destructive tests to predict concrete strength. Non-destructive tests on column and cube specimens during concrete curing. Influence of different core diameters on in-place concrete strength predictions. Investigation of core strength variation depending on the drilling position. Identification of cores number to calibrate accurate correlation laws for NDT tests. Abstract: This research work presents the results of an experimental campaign performed on column specimens to investigate the capacity of destructive coring test and non-destructive tests to predict the in-place concrete strength. The considered non-destructive tests are Surface Hardness (SH) and Ultrasonic Pulse Velocity (UPV) ones. Using these tests' results also SonReb method is applied. The peculiarity of this research is that the results of all the performed test on the columns are compared to results obtained from cube specimens made with the same concrete of the columns. The non-destructive predictive methods are performed on both column and cube specimens during the curing of the concrete at different ages, while the destructive coring test on columns specimens at 28th day after casting. A discussion on the comparison between drilled cores' strength, determined using provisions of different building codes, and cube specimens' strength is provided. In particular, the code providing the safest concrete strength predictions is identified. Moreover, the influence of different core diameters on the evaluation of in-place concrete strength is analyzed. The variation of core specimens' strength, depending on the position of test execution along the columns' height, is also investigated. To assess the in-place concrete strength by non-destructive tests, correlation formulae are calibrated on the bases of cores strength determined according to ACI Code. The prediction ability of these formulae is assessed. Results obtained from SH and UPV tests at different concrete ages are compared to the cube specimen strength at the same ages, and the influence on the measured parameters of different moisture conditions during curing is analyzed. The minimum number of cores to adequately predict the in-place concrete strength by means of SH and UPV methods is also determined. Best predicting SonReb formulations are identified.